1999
DOI: 10.1021/jp983273d
|View full text |Cite
|
Sign up to set email alerts
|

Rate Constants for the Reactions of Hydroxyl Radical with Several Alkanes, Cycloalkanes, and Dimethyl Ether

Abstract: Relative rate experiments were used to measure ratios of rate constants as a function of temperature for the reactions of OH with propane, n-butane, n-pentane, n-hexane, cyclopropane, cyclobutane, cyclopentane, cyclohexane, and dimethyl ether. To assure internal consistency, ratios were measured for seventeen reactant pairs among these reactants. All of the derived rate constants are based on an absolute rate constant of the OH + C2H6 reaction using k(ethane) = 1.0 × 10-11 exp(−1094/T) cm3/molecule s. The rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
132
1

Year Published

2002
2002
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(160 citation statements)
references
References 30 publications
27
132
1
Order By: Relevance
“…The rate constants derived from the relative rate studies of Baker et al (1970) (as re-evaluated by , Hucknall et al (1975), Atkinson et al (1982b), Edney et al (1986), Behnke et al (1987), Finlayson-Pitts et al (1993) and DeMore and Bayes (1999) are in generally excellent agreement with the recommendation, to within 7%, 5%, 2%, 3%, 15%, 4% and 8%, respectively. The rate constants derived from the relative rate measurements of DeMore and Bayes (1999) trend from being 2% higher than the recommendation at 428 K to being 7% lower than the Atmos.…”
Section: Oh+propanementioning
confidence: 53%
See 4 more Smart Citations
“…The rate constants derived from the relative rate studies of Baker et al (1970) (as re-evaluated by , Hucknall et al (1975), Atkinson et al (1982b), Edney et al (1986), Behnke et al (1987), Finlayson-Pitts et al (1993) and DeMore and Bayes (1999) are in generally excellent agreement with the recommendation, to within 7%, 5%, 2%, 3%, 15%, 4% and 8%, respectively. The rate constants derived from the relative rate measurements of DeMore and Bayes (1999) trend from being 2% higher than the recommendation at 428 K to being 7% lower than the Atmos.…”
Section: Oh+propanementioning
confidence: 53%
“…An Arrhenius plot of the absolute and relative rate data of Talukdar et al (1994), Mellouki et al (1994), Clarke et al (1998), DeMore and Bayes (1999) and Kozlov et al (2003) for temperatures <300 K is shown in Fig. 6.…”
Section: Oh+propanementioning
confidence: 99%
See 3 more Smart Citations